A (des)construção da elitização e a possibilidade de democratização do ensino superior: um estudo da política de cotas no Curso de Medicina da Universidade Federal da Paraíba - Araújo, Luciano Rufino de (2020)
This study is the result of a Master's degree research developed under the Postgraduate Program in Management, Higher Education Evaluation - MPPGAV- Professional Master's Degree. It aims to analyze the UFPB Medicine Course based on the Quota Policies adopted by universities, based on the premise that the inclusion of different socio-ethnic-racial groups occurring through affirmative public policies would enable more democratic internal processes and reconfigurations of the course. We will try to problematize a possible process of (und) construction of the historical elitist condition of the medical course. We assume that the adoption of vacancy reserve policies causes a "structural imbalance" that has long been settled in the Brazilian Public University - because it is historically considered a space that is not visited by certain social strata, such as blacks, Indians, people with special needs and students from the public school - these structural imbalances we are referring to are, therefore, the massive change in the social, ethnic and cultural profile of the public that ascends to that educational level, being guaranteed to these collectives reserves of vacancies in the graduation courses of the Brazilian IFES. This new reality provokes new phenomena within the academic universe that need new looks. It was intended to know and problematize the processes of massification of Higher Education in Brazil and the possibility of (re) knowing democratization movements in socially legitimized courses of high social prestige. We submit the data analyzes based on Martin Trow's Theory on the Elites System along with Ristoff's postulates. And the theoretical approaches of Souza (2017) and Bourdieu (2015). The data show the significant change of the socioeconomic profile of the students of the course. The interviews, together with field observations, reveal contradictions that still persist, but point to the beginning of other processes of democratization and deconstruction of the elitism of the UFPB Medicine Course.